Tinospora Sinensis Compounds for Zika Virus Targets 5JRZ and 5KVD In Silico Screening: A Potential Approach to Preventing Guillain-Barre Syndrome - Pradyum Prasad; Samiksha Bhor (International Journal of Cell Biology and Cellular Functions, 2023)
Objective: GBS is a very rare kind of disease but at the same time, it is very dangerous too. The study estimates that people who are suffering from zika virus infection are more prone to GBS. According to surveys, 1 out of 4000 people got affected by this disease, and the scariest part of this disease is that there is no cure available. In this computational era drug discovery is also done by computational methods nowadays, we choose 5JRZ and 5KVD as our target proteins to perform the molecular docking. Methods: The study was based on a computational approach using several types of phytocompounds for the estimation of their potential against the selected target proteins 5JRZ and 5KVD. In the process of molecular docking, different types of software and online tools will be needed to perform different types of tasks. The online tools and software are IMPPAT, PubChem, PDB, OpenBable, BIOVIA Discovery Studio, PDBsum, PyRx and Swissadme. Result: The molecular docking result revealed that the selected ligands have the best binding affinity with both the target proteins. Conclusion: The ligands could potentially be used to suppress the triggers of the GBS that will eventually treat the GBS, these findings will help researchers to find novel drugs against the GBS and Zika virus infection.
Keywords: 5JRZ; 5KVD; GBS; Tinospora sinensis; molecular docking